2007
DOI: 10.1002/adma.200602605
|View full text |Cite
|
Sign up to set email alerts
|

Fungus‐Based Synthesis of Chemically Difficult‐To‐Synthesize Multifunctional Nanoparticles of CuAlO2

Abstract: Fungal nanosynthesis of ternary CuAlO2 phase is achieved at 50 °C. This phase is chemically difficult to synthesize at low temperatures because of the incompatible oxidation chemistry of Cu and Al. The synthesized protein‐capped water‐dispersible nanoparticles show blue luminescence and radio‐frequency absorption (see figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 35 publications
(22 reference statements)
0
23
0
Order By: Relevance
“…Recent advances in material technology allow the synthesis of innovative heat transfer fluids with enhanced transport and thermal properties by suspending nanoparticles in base fluids [9]. Generally, nanofluids possess some remarkable properties, such as less clogging problem, reduced heat transfer system size, higher thermal conductivity, better stability, and lower pressure [10,11]. In recent years, different scientific endeavors have been carried out in the quest of new nanofluid composites with improved parameters [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in material technology allow the synthesis of innovative heat transfer fluids with enhanced transport and thermal properties by suspending nanoparticles in base fluids [9]. Generally, nanofluids possess some remarkable properties, such as less clogging problem, reduced heat transfer system size, higher thermal conductivity, better stability, and lower pressure [10,11]. In recent years, different scientific endeavors have been carried out in the quest of new nanofluid composites with improved parameters [12].…”
Section: Introductionmentioning
confidence: 99%
“…12,14,[16][17][18][19]26 In terms of defect emission, only two reports could be found in the literature indicating the presence of defect luminescence, again with signicantly different peak positions being reported. In the spectra reported by Chiu et al an additional emission centred around 428 nm was observed, while Fang et al observed two additional bands at 470 nm and 590 nm ascribed to copper vacancies and interstitial oxygen respectively.…”
Section: 15mentioning
confidence: 99%
“…[7][8][9][10][11] Additionally, more exotic methods such as polymer assisted deposition and fungus assisted synthesis have also been demonstrated. 12,13 Despite this rapid advance, many questions remain, particularly with respect to the intrinsic band gap and optical properties of this material. To date, most optical studies have focused on absorption measurements of thin lms or single crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical routes are toxic and require extremes of temperature, while the physical ones are expensive and laborious. Unlike these, biological routes for the synthesis of nanoparticles have recently been developed and yield nanoparticles at room temperature and physiological pH, with properties such as high stability, water dispersal, fluorescence, etc., which are very difficult to achieve by chemical and physical routes [16][17][18][19][20][21][22]. Moreover, biologically synthesized nanoparticles are naturally …”
mentioning
confidence: 99%